“In the End You Keep Silent”: Help-Seeking Behavior Upon Sexual Victimization in Older Adults - Nobels, Anne (Journal of interpersonal violence, 2024)
Sexual violence is considered a prominent mental health problem. Exposure to sexual victimization during lifetime has been linked to mental health problems in old age. Research in adult victims has shown that they experience many barriers for disclosure and seeking professional help upon sexual victimization. However, information on help-seeking behavior in older victims of sexual violence is non-existent. With this study we aim for a better understanding of help-seeking behavior upon sexual violence in older adults. We used a mixed methods approach with an explanatory sequential design. Data were collected through structured face-to-face interviews with a random sample of 227 sexual violence victims of 70 years and older living in Belgium. Quantitative data were triangulated with qualitative data from 15 in-depth interviews with older victims. We found that up to 60% of older sexual violence victims never disclosed their experiences and 94% never sought professional help. Help-seeking is a complex process comprising several phases, which are affected by strong feelings of shame and self-blame, ageist premises and taboos about sexuality. In the end, most victims choose to cope on their own. Occasional disclosure only happens decades after the sexual violence took place. Older victims do not spontaneously disclose to healthcare workers but expect professionals to initiate the conversation. In conclusion, few older victims disclose or seek professional help upon sexual victimization. Healthcare professionals working with older adults need capacity building through training, screening tools, and care procedures to initiate conversation on sexual violence, and to detect signs, prevent, mitigate and respond to sexual victimization in older adults.